Kualitas Pelayanan Pada Balai Besar Pelatihan Kesehatan Kementerian Republik Indonesia Cilandak - Jamilatusa Sarifah; Dini Gandini Purbaningrum (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
This research is aqualitative research that aims to describe the Quality of Service Delivery of Cancer Health Training Pusdiklat Ministry of Health of the Republic of Indonesia and describes and analyzes the inhibiting and supporting factors for instructors in serving training participants at the Pusdiklat Health. Health services are activities or a series of activities to fulfill the service needs determined by law for each instructor, trainee and/or administrative services provided by the service provider. study uses the theory of quality of health services according to Kotler in Fendy Tjibtono (2016: 284), namely Assurance (guarantee) Emphty (empathy) Reliability (reliability) Responsiveness (responsiveness) Tangible (physical appearance), Quantity timeliness, effectiveness, independence and commitment work, analysis of research data is descriptive. Perfect research results. In terms of realism indicators, it has not worked perfectly, such as the skills of officers in using supporting facilities in the service process. On the responsive indicator, all officers who carry out health training services are classified as responsive to training participants. Assurance indicators in health training centers are very much determined by the performance of health services. Tangible indicators in the form of the appearance of the apparatus when carrying out services, comfort right when the service takes place. The Empathy Indicator puts the interests of training participants first, serves in a friendly, courteous and courteous manner, officers do not discriminate and are able to respect training participants.